3D pore-scale simulations and 1D volume-averaged calculations of the flow and thermal non-equilibrium for low-velocity filtration combustion. (October 2021) - Shi, Junrui; Lv, Jinsheng; Behrendt, Frank; Liu, Yongqi; Mao, Mingming; He, Fang
Highlights: Insight into pore scale processes of low-velocity filtration combustion is provided. Estimation expression for root mean of average gas temperature is proposed. Non-equilibrium exists in the full bed for filtration combustion. Flow and thermal non-equilibrium in the bed is accelerated with mixture velocity. The computational time increases 225 time by the 3D pore scale model. Abstract: 3D pore-scale simulations of the flow and thermal non-equilibrium for low-velocity filtration combustion are numerically performed in randomly packed bed of 2282 pellets with a diameter of 5.6 mm. A 1D volume-averaged simulation is also conducted for comparison. The root-mean-square (RMS) of variables is used to quantitatively study the non-equilibrium characteristics. Results show that the 1D model underpredicts the flame thickness. Predictions by the 3D pore-scale model show that the flow and thermal non-equilibrium exist in the entirely packed bed for all the conditions investigated, but the extent of flow and thermal non-equilibrium in the packed bed varies with time and operating condition. An estimation expression for the root mean of the average gas temperature is proposed using the mixture gradient and the ratio between the average axial velocity and its value of RMS. With increasing mixture inlet velocity, the extent of the flow and thermal non-equilibrium increases, demonstrating that the spatially inhomogeneous variation of the mixture velocity and gas temperature in the packed bed is accelerated with mixture velocity at the inlet. It is observed that the computational time of the 3D pore-scale model is higher by a factor of 225 compared with the 1D volume-averaged model.